2019
DOI: 10.3390/magnetochemistry5010016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Magnetic Fields on Phase Transformations in Amorphous Nd2Fe14B

Abstract: We briefly summarize the results from a set of experiments designed to demonstrate the effects of high magnetic fields applied during thermal annealing of amorphous Nd2Fe14B produced through melt-spinning. A custom-built differential scanning calorimeter was used to determine the crystallization temperatures in zero-field and in applied fields of 20 kOe and 90 kOe, which guided subsequent heat treatments to evaluate phase evolution. X-ray diffraction was used for phase identification and transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…101,102 Perhaps the most consistently observed phenomenon observed when applying strong magnetic fields during annealing treatments is a refinement of the microstructure when compared with no-field annealing. Exploration into thermomagnetic processing of ferrous alloys have the greatest body of literature demonstrating this effect, 95,103,104 though several magnet material systems have demonstrated it as well, including Nd-Fe-B 105,106 and Pr-Co-B 107 systems. The mechanisms underlying this effect are not well understood due to the interplay of thermodynamic and kinetic processes.…”
Section: Thermomagnetic Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…101,102 Perhaps the most consistently observed phenomenon observed when applying strong magnetic fields during annealing treatments is a refinement of the microstructure when compared with no-field annealing. Exploration into thermomagnetic processing of ferrous alloys have the greatest body of literature demonstrating this effect, 95,103,104 though several magnet material systems have demonstrated it as well, including Nd-Fe-B 105,106 and Pr-Co-B 107 systems. The mechanisms underlying this effect are not well understood due to the interplay of thermodynamic and kinetic processes.…”
Section: Thermomagnetic Processingmentioning
confidence: 99%
“…For the Nd-Fe-B system, heating near-amorphous ribbons in magnetic fields of 0 T to 9 T revealed an unchanged crystallization temperature, but slower growth at a given annealing temperature as the applied field increased. 105 The Pr-Co-B system was impacted by thermodynamic effects due to the stabilization of the high-moment, ferromagnetic 2:17 phase. 107 While the microstructure was significantly refined as the field increased (Fig.…”
Section: Thermomagnetic Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further motivating experiments in high static field thermal analysis are the observations of significant rate and magnetic field-dependent changes in microstructural morphology and phase equilibria that have been observed from microstructural analysis and dilatometry. These observations have been described theoretically through evaluation of the magnetic component in Gibbs free energy [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, the domain of applying a high magnetic field (HMF) to materials processing has undergone extremely rapid growth since the development of superconducting magnet technology. Especially in the solidification process of materials, HMFs have exhibited a special capacity to modify the crystal growth and thus the final microstructure and crystallography because of the induced Lorentz force, magnetic torque, magnetization energy, etc. Morikawa et al obtained aligned primary dendrite arms of MnBi along the HMF direction in the Bi–Mn alloy. Liu et al reported a decrease of the secondary dendrite arm spacing by the HMF in the solidification of Al–Li alloy.…”
Section: Introductionmentioning
confidence: 99%